Drought-induced root plasticity of two upland NERICA varieties under conditions with contrasting soil depth characteristics. (2nd July 2016) - Menge, Daniel Makori; Kameoka, Emi; Kano-Nakata, Mana; Yamauchi, Akira; Asanuma, Shuichi; Asai, Hidetoshi; Kikuta, Mayumi; Suralta, Roel Rodriguez; Koyama, Takuya; Tran, Thiem Thi; Siopongco, Joel D. L. C.; Mitsuya, Shiro; et al.
Abstract: To identify differences in root plasticity patterns of two upland New Rice for Africa (NERICA) varieties, NERICA 1 and 4, in response to drought under conditions with contrasting soil profile characteristics, soil moisture gradients were imposed using a sloping bed system with depths ranging 30–65 cm and a line-source sprinkler system with a uniformly shallow soil layer of 20 cm depth. Varietal differences in shoot and root growths were identified only under moderate drought conditions, 11–18% v/v soil moisture content. Further, under moderate drought soil conditions where roots could penetrate into the deep soil layer, deep root development was greater in NERICA 4 than in NERICA 1, which contributed to maintaining dry matter production. However, under soil conditions with underground impediment to deep root development, higher shoot dry weight was noted for NERICA 1 than for NERICA 4 at 11–18% v/v soil moisture content, which was attributed to increased lateral root development in the shallow soil layer in NERICA 1. Enhanced lateral root development in the 0–20-cm soil layer was identified in NERICA 1 even under soil conditions without an impediment to deep root development; however, this did not contribute to maintaining dry matter production in upland rice. Thus, we show different root developmental traits associated with drought avoidance in the two NERICA varieties, and that desirable root traits for upland rice cultivation vary depending on the target soil environment, such as the distribution of soil moisture and root penetration resistance.